Juridical Review of Medical Malpractice in Criminal Law in Indonesia (Decision Analysis No.182/Pdt.G/2016/Pn.Jkt.Tim) - Dominiques Reggy Marfilan Tinggogoy; Nanda Dwi Rizkia; Hardi Fardiansyah (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The increase in malpractice cases in Indonesia is caused by doctors' errors or negligence in carrying out medical procedures on patients. This causes dissatisfaction among patients, who feel their rights have been violated and want to sue the doctor who harmed them. Mistakes made by doctors and health workers are actions that are very detrimental to patients when carrying out treatment, which can result in deterioration of the patient's health or death. Mistakes in medical practice result in criminal liability. Therefore, it is necessary to have special legal certainty in the health care system so that injured patients can obtain legal justice. The method used in this research is normative legal research method